Are We Susceptible to Rowhammer? An End-to-End Methodology for Cloud Providers - Cojocar, Lucian; Kim, Jeremie; Patel, Minesh; Tsai, Lillian; Saroiu, Stefan; Wolman, Alec; Mutlu, Onur (IEEE Symposium on Security and Privacy (S&P), 2020)
Cloud providers are concerned that Rowhammer poses a potentially critical threat to their servers, yet today they lack a systematic way to test whether the DRAM used in their servers is vulnerable to Rowhammer attacks. This paper presents an end-to-end methodology to determine if cloud servers are susceptible to these attacks. With our methodology, a cloud provider can construct worst-case testing conditions for DRAM. We apply our methodology to three classes of servers from a major cloud provider. Our findings show that none of the CPU instruction sequences used in prior work to mount Rowhammer attacks create worst-case DRAM testing conditions. To address this limitation, we develop an instruction sequence that leverages microarchitectural side-effects to ``hammer'' DRAM at a near-optimal rate on modern Intel Skylake and Cascade Lake platforms. We also design a DDR4 fault injector that can reverse engineer row adjacency for any DDR4 DIMM. When applied to our cloud provider's DIMMs, we find that DRAM rows do not always follow a linear map.